AMBIVALENSI PEMAKNAAN EKSISTENSIAL DALAM PUISI BIBLIKAL; TELAAH FILOSOFIS TERHADAP KUMPULAN PUISI PERTARUNGAN DI PNIEL - Giovanni Aditya Lewa Arum (Program Studi Filsafat Universitas Katolik Widya Mandira Kupang, 2021)
The biblical poems are the poems that takes their inspiration from the Bible. It means the Bible becomes the hyporgram for the poems. One of the poetic signs is the biblical imagery. Cyprian BitinBerek is one of the poets who pays much attention on biblical poems. Pertarungan di Pniel gathers all of poems that take their inspiration from the Bible. This essay is a critical exploration. This critical exploration uses two theories as its apparatus, i.e: exegetical theory and philosophical theory. This essay uses the existential philosophy from Kierkegaard to criticize some poems that covers existential philosophy issues. Finally, the writer finds two critical conclusion, i.e: There are the tendency of subjective extortion that out of the narrative tradition from Old Testament and the ambivalence of existential signification from some biblical poems. In the end of this essay, the writer gives some positive points from Cyprian’s biblical poems.